The Effects of Ketogenic Diet on Seizures, Cognitive Functions, and Other Neurological Disorders in Classical Phenotype of Glucose Transporter 1 Deficiency Syndrome - Gumus, Hakan; Bayram, Ayşe Kaçar; Kardas, Fatih; Canpolat, Mehmet; Çağlayan, Ahmet Okay; Kumandas, Sefer; Kendirci, Mustafa; Per, Huseyin (Neuropediatrics, 2015)
Objectives The purpose of this study was to characterize patients who were diagnosed with glucose transporter protein 1 deficiency syndrome (Glut1D), and also to assess the efficacy of ketogenic diet (KD) therapy on seizure control, cognitive functions, and other neurological disorders.Patients and Methods We studied six unrelated patients with the classical phenotype of Glut1D, focusing on clinical and laboratory features, the KD therapy and outcome over the 25-month follow-up period.Results Five patients became seizure-free with the onset of ketosis, and anticonvulsants were discontinued. Other neurological features such as ataxia, spasticity, and dystonia showed a less striking improvement than seizure control. There was no significant change in the intelligence quotient (IQ) level or microcephaly. In all patients, alertness, concentration, motivation, and activity resulted in a moderate improvement of variable degree. The early-onset adverse effects of KD were observed in five patients. The KD regimen failed in one patient, therefore, his diet was changed with an alternative to KD.Conclusions Treatment with KD resulted in a marked improvement in seizures and cognitive functions but its effect appeared to be less striking on the other neurological disorders of the patients. When the classic KD is not tolerated, an alternative to KD may be helpful.
Keywords: glucose transporter protein 1 deficiency syndrome; ketogenic diet; cognitive functions; seizures; children